2011
DOI: 10.1002/jwmg.220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implanted satellite transmitters on behavior and survival of female common eiders

Abstract: Surgically implanted satellite transmitters have been widely used in studies of avian ecology, yet little is known about their potential impacts on birds. We implanted satellite transmitters with percutaneous antennae (approx. 50 g) in 17 female common eiders (Somateria mollissima) at a breeding colony in Arctic Canada. Among females implanted during incubation, 11 of 12 nests were abandoned within 1 week of being radioed. We observed no differences in the proportion of time that implanted female eiders alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
(37 reference statements)
0
16
1
Order By: Relevance
“…Given these differences in relative weight of transmitters and their effects, we cannot determine whether any effect of transmitters on females would have been more like harlequin ducks or eiders. We found, however, no support for a time effect ( t + 1 vs. > t + 1) on apparent survival, as was observed by Fast et al (). Eiders also were carrying relatively larger transmitters than were scoters in our study, and eiders may experience harsher environmental conditions associated with arctic winter habitats (Mosbech et al ), which presumably could make them more sensitive to energetic constraints associated with transmitters than scoters wintering along the milder Pacific coast (Gurney et al ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Given these differences in relative weight of transmitters and their effects, we cannot determine whether any effect of transmitters on females would have been more like harlequin ducks or eiders. We found, however, no support for a time effect ( t + 1 vs. > t + 1) on apparent survival, as was observed by Fast et al (). Eiders also were carrying relatively larger transmitters than were scoters in our study, and eiders may experience harsher environmental conditions associated with arctic winter habitats (Mosbech et al ), which presumably could make them more sensitive to energetic constraints associated with transmitters than scoters wintering along the milder Pacific coast (Gurney et al ).…”
Section: Discussioncontrasting
confidence: 85%
“…Esler et al () observed no effects of intra‐abdominal transmitters on apparent survival in harlequin ducks ( Histrionicus histrionicus ) wintering in Alaska, after 2 weeks post‐deployment. Fast et al (), however, reported a 20% reduction in apparent survival for common eider ( Somateria mollissima ) females marked with transmitters of similar design, but only in the first year post‐marking. They attributed this effect to reduced true survival or permanent emigration.…”
Section: Discussionmentioning
confidence: 99%
“…Although implanting eider females with transmitters could potentially impact their survival (Fast et al . ), preliminary analysis showed that incorporating females tracked by satellite did not affect our results for the Canadian population.…”
Section: Methodsmentioning
confidence: 79%
“…The implantation of satellite transmitters with external antennas in Common Eiders Somateria mollissima during incubation led to the abandonment of 11 out of 12 nests in a Canadian study, but 30% of the tagged birds were observed nesting in the following years. Furthermore, the tagged birds spent more time preening than colourringed birds and suffered a 20% decrease in survival during the first year after surgery compared to the control group [25]. Limping was observed in some individuals, something which was also found by 1 out of the 6 Common Eiders in the study of Latty et al [49].…”
Section: Abdominal Implantsmentioning
confidence: 77%